Impact of the plyometric training on the vertical jump performance - case of young soccer players under U12s / Zerf Mohammed - Mohammed, Zerf (Faculty of Sports Science and Recreation, 2017)
Muscle strength is an essential factor to perform effectively kicks, tackles, jumps, sprints and prevent injuries in the soccer game (Benítez Sillero, J.D.; Da Silva-Grigoletto, M.E.; Muñoz Herrera, E.; Morente Montero, A. yGuillén del Castillo, M, 2015). Whereas to simulate the explosive strength needed in athletics, Verkhoshanski' introduced the Plyometrics (William D. Bandy, Barbara Sanders, 2007) that (Bram Swinnen, 2016) confirms its. However, little research has been done to investigate injury risk with plyometric training considerations. Where some authors suggest that plyometric exercises should not be performed by children (Jason Brumitt, Human Kinetics, 2010) or an individual who has not attained puberty (Edward McNeely, David Sandler, 2006). Design: the effects of Plyometrics training on vertical jump performance have been widely researched. Where some authors reported its effectiveness in vertical jump, while others reported no significant effects. Methods: for propose, our experimental protocol was integrating in the program of the coach for a period of 6 weeks as a 20 minutes’ time Plyometrics works per week session as additional exercises in the benefit of the experimental group. Results: Our results confirm the benefits of Plyometric training to improve the Vertical Jump Performance among young soccer players under U12s years where the experimental group is accrual performance than the control group. Conclusions: the pubescent athletes can engage in low- to medium-intensity Plyometrics.